Evaluation of Plasma Alpha Klotho Levels in Obese Cases: Plasma Alpha Klotho Levels in Obese Cases - Solak, Ibrahim; Guney, Ibrahim; Sekmenli, Nevin; Kurku, Huseyin; Eryilmaz, Mehmet Ali (Journal of Medical Biochemistry, 2026)
Background: Klotho is an anti-aging gene that lengthens life when excessively expressed and accelerates aging when disrupted. In our study, we will research the correlations between plasma α-Klotho (α-KL) protein levels with body mass index (BMI), carotid intima media thickness (CIMT), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), high-sensitivity c-reactive protein (hsCRP) and cholesterol values in obese patients.Methods: This study was conducted in a single-centered and cross-sectional manner.Results: The study was performed with a total of 90 participants, 35 women (38.9%) and 55 men (61.1%). Of participants included in the study, 30 were normal weight (33.3%) (Group 1), 30 were overweight (33.3%) (Group 2) and 30 were obese (33.3%) (Group 3). There were statistically significant differences in the α-KL protein (p=0.010), hsCRP (p
Keywords: carotid intima media thickness, klotho, obesity, oxidative stress,